Selective production of C9 monomeric phenols via hydrogenolysis of lignin using Pd-(W/Zr/Mo oxides)-supported on biochar catalyst - Gurrala, Lakshmiprasad; Kumar, M. Midhun; Sharma, Shweta; Paek, Changyub; Vinu, R. (Fuel, 2022)
Valorizing lignin to phenolic monomers and fine chemicals is an essential component of a sustainable biorefinery that uses lignocellulosic feedstocks. In this study, Pd-metal oxides (ZrO2, WOx, MoO3) supported on activated biochar (ABC) catalysts were developed for hydrogenolysis of lignin. The metals (2% Pd, 5% Zr, 5% W, 5% Mo) were supported on activated biochar using the wetness impregnation method, and the catalysts were extensively characterized. The effect of addition of secondary metals on active surface properties such as acidity, Pd metal particle size and dispersion were also evaluated. The selectivity to C9 monomeric phenols followed the trend: 2Pd-5Mo/ABC (57.3%) > 2Pd-5Zr/ABC (49.2%) > 2Pd-5W/ABC (45%) > 2Pd/ABC (42.9%). The maximum C9 phenolic monomer yield achieved in this study was similar to 22 wt%. The fractional conversion of lignin was 67-69% with Pd-metal oxide catalysts. The presence of Mo in the catalyst inhibited the hydrogenation of aliphatic C-alpha = C-beta in lignin and led to the formation of t-isoeugenol, while the presence of W and Zr resulted in selective formation of the hydrogenated product, propyl guaiacol. Using model compounds, it is proved that the formation of propyl guaiacol is via hydrogenation of t-isoeugenol, and not through dehydroxylation of propanol guaiacol. The dehydroxylation activity of the catalysts is attributed to the higher Lewis acidity and electropositive nature of the metals. A notable carbon atom economy of 47-50% towards total phenolic monomers was achieved with 2Pd/ABC, 2Pd-5Mo/ABC and 2Pd-5Zr/ABC catalysts.
Keywords: Activated biochar; Guaiacol; Hydrogenolysis; lignin; Metal oxides; Palladium

Unraveling the reaction mechanism of selective C9 monomeric phenols formation from lignin using Pd-Al2O3-activated biochar catalyst - Gurrala, L.; Kumar, M. M.; Yerrayya, Attada; Kandasamy, Prabu; Castano, Pedro; Raja, T.; Pilloni, Giovanni; Paek, C.; Vinu, R. (Bioresource Technology, 2022)
The conversion of biomass-derived lignin to valuable monomeric phenols at high selectivity is of paramount importance for sustainable biorefineries. In this study, a novel Pd-Al2O3 supported on activated biochar catalyst is developed for lignin hydrogenolysis. The catalyst characterization revealed that the (1 1 1) planes of both of Pd-0 and Al2O3 were exposed to the surface. The maximum lignin conversion of 70.4% along with high liquid yield (similar to 57 wt%) was obtained at 240 degrees C, 3 h and 3 MPa H-2 pressure. The total monomeric phenols yield in the liquid was 51.6 wt%, out of which C9 monomeric guaiacols constituted similar to 30.0 wt% with 38.0% selectivity to 4-propyl guaiacol. Using the reaction intermediate, coniferyl alcohol, chemoselective hydrogenation of C-alpha=C-beta is proved to occur over the Pd site, while dehydroxylation of C-gamma-OH is shown to occur over the alumina site. An impressive carbon atom economy of 60% was achieved for the production of monomeric phenols.
Keywords: Hydrogenolysis; lignin; Mechanism; Pd-Al/activated biochar; Propanol guaiacol; Propyl guaiacol